Pengembangan LKS pada Materi Mendemonstrasikan Naskah Drama Berbasis Kearifan Lokal Siswa Kelas XI SMA Negeri 1 Unggulan Lubuklinggau - Tiya Handayani; Satinem Satinem; Sri Murti (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The student worksheets (LKS) used so far are still textual without regard to the local wisdom where students live. For this reason, it is necessary to develop LKS based on local wisdom so that students are more motivated to learn and understand teaching material. This study aims to describe the feasibility of developing worksheets on the material demonstrating the play of scripts based on local wisdom of class XI students of SMA Negeri 1 Unggulan Lubuklinggau seen from the level of validity, practicality, and effectiveness. The research method used is Dick & Carey's Research and Development (R&D) model. Data collection techniques using interviews, questionnaires, and tests. The test results were analyzed by paired sample t-test with SPSS version 16. This research has produced a new product in the form of LKS on the material demonstrating a valid, practical and effective local wisdom based script so that it is suitable to be used. Based on the calculation results show that the t-test is greater than 3.648, 1.697, then it can be concluded that Ho is rejected and Ha is accepted. Test results on the paired samples test output indicate that the value of sig. is 0,000 smaller 0.05 so Ho is rejected. So, there is a significant difference between the values ​​before and after using teaching materials to demonstrate LKS scripts based on local wisdom